(untitled) (Medico Legal Update, 2020)
Background: The purpose of this study was to investigate the effects of Swedish massage on anxiety and pressure pain threshold in office workers with psychological stress. Method: Sixty office workers with psychological stress were randomly assigned to experimental group 1 and control group. They were assigned into either a Swedish massage group (Experimental group 1, n = 30) or a resting group (Control group, n = 30). A single measurement mediated Swedish massage and rest for 20 minutes and was measured before and after intervention. Findings: In state trait anxiety inventory (STAI), there were significant differences between before and after the experiment and between the two groups (p<.05). The pressure pain threshold (PPT) of the upper trapezius increased in the Swedish massage group (p<.05). Application: These findings indicate that, the Swedish massage applied to stressed office workers showed a significant difference in increase of PPT and decrease of STAI.